KAJIAN PARAMETER MARSHALL DENGAN SUBSTITUSI BAN DALAM BEKAS KENDARAAN SEBAGAI ASPAL PANAS PADA CAMPURAN ASPAL BETON (AC-BC) - Adry Kal Muna; Romaynoor Ismi; Idayani (Fakultas Teknik - Universitas Al Muslim - Bireuen Aceh- Indonesia, 2025)
Roads are transportation infrastructures constructed to meet human mobility needs. Initially, roads developed from compacted soil formed by human footprints and evolved along with the advancement of civilization. In modern practice, asphalt concrete pavements, particularly Asphalt Concrete Binder Course (AC-BC), are widely used. Meanwhile, the increasing production of waste tires, which is not balanced by proper management, poses a significant environmental threat. One potential solution is the utilization of motorcycle inner tube waste as a substitute material in hot asphalt mixtures. In addition, roads play a crucial role in supporting economic activities. However, pavement layers, especially AC-BC, frequently experience damage such as cracking and potholes due to the continuously increasing traffic loads. To address this issue, motorcycle inner tube waste can be incorporated into asphalt concrete mixtures to enhance pavement performance. This study aims to evaluate the effect of substituting motorcycle inner tube waste as part of the hot asphalt binder in AC-BC mixtures. The substitution percentages used were 0%, 1%, 2%, 3%, and 4% by weight of asphalt, with an additional parameter of water immersion for 30 minutes at a temperature of 60°C. The research methodology began with evaluating the aggregate gradation, followed by the design and preparation of test specimens with varying asphalt contents to determine the Optimum Asphalt Content (OAC). Subsequently, specimens incorporating inner tube waste were prepared and tested using the Marshall method. The results indicate that the characteristics of the 60/70 penetration asphalt mixture, in terms of both physical properties of asphalt and aggregates, meet the required specifications. This suggests that the use of waste inner tubes in asphalt mixtures improves load-bearing capacity with relatively low deformation. The optimum substitution level was found at 2%, yielding a stability value of 1603 kg.